Human Resources Empowerment On Community Learning Activities Center In Tulungagung East Java Indonesia - Mastur, Mastur (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
The purpose of the study is to know the process of management learning activities center following planning, organizing, implementation, controlling, and evaluation. To knows human resources empowerment community Learning activities center with a tutor and professional teacher, interviewer, and conduct research for teacher, tutor, and student. This study used a qualitative approach with the case study. The research location is CommunityCommunity Learning activities center Wahyu Surya Pelangi Campurdarat, Nurani Tanggung Campurdarat and Sinar Pagi Pagerwojo Kabupaten Tulungagung. The data collection technique is used observation, dept interview, and documentation. Data analysis on individual case studies uses the Miles dan Huberman model use data reduction, data display, and conclusion drawing, data analysis cross-case with comparative analysis recommended by Yin (2002). Data reliability is used for credibility, transferability, dependability, and conformability. The result of the study: First, the management process of PKBM Tulungagung Jawa Timur Indonesia includes (a) planning used to decide the program conducted by PKBM, aim, and solution to face the obstacle raised (b) Organizing used to divide many classes suitable with ages, in other that can be differences between young and old learner, and organizational management structure PKBM with decided each task (c) the role implementation is to decide who can run the program PKBM, who as a teacher, and who as a student, and who as a person responsible of the program, and (d) The function of evaluation is to assess the program conducted or running, and decided the solution of obstacles. Second, human resources empowerment on PKBM Tulungagung Jawa Timur Indonesia. Many activities of empowerment are: (a) teaching activities taught by professionals, (b) giving training to the teacher to increase their skill to teach young and old learners (c) giving add programs of education and skill such as vocational, culinary art, etc. (d) incurring tutor from partner agency to give socialization for student, (e) Implementation the program of PKBM planned before, and (f) selection professional teacher will teach in PKBM.